Language and Discourse in Special Education : Understanding Ethnographic Interdisciplinary Team Culture - Manor-Binyamini, Iris (Springer International Publishing : Imprint: Springer, 2015)
Interdisciplinary teamwork has significantly improved the education of children with special needs. Because the students' needs are complex, the responses of the diverse professionals working together to provide services must be equally multifaceted.   Language and Discourse in Special Education analyzes how interdisciplinary teams work in school settings, specifically how members convey their knowledge in collaboration with others. Results from an in-depth study conducted in a school for students with intellectual and developmental disabilities illustrate the evolution of team culture, from establishing a common language to sharing information to solving day-to-day problems. The book details how educators, therapists, and doctors integrate concepts from their distinct fields and apply this shared knowledge in dealing with students, the administration, and one another. These observations support theoretical models of how teams can most effectively address student needs and identify optimal conditions for meaningful collaboration.   Featured areas of coverage include:   The importance of interdisciplinary teamwork in special education Methods used in analyzing language and discourse Key words relating to the team's work with the students Discourse events within the team and with the administration A practical model for interdisciplinary teamwork   Language and Discourse in Special Education is an essential reference for researchers, professionals, and graduate students working with special needs students in child and school psychology, behavioral therapy (e.g., occupational, psychical, speech), social work, pediatric medicine, and allied mental health and medical fields.